Overcoming Barriers of Age to Enhance Efficacy of Cancer Immunotherapy: The Clout of the Extracellular Matrix - Owyong, Mark; Efe, Gizem; Owyong, Michael; Abbasi, Aamna J.; Sitarama, Vaishnavi; Plaks, Vicki (Frontiers in Cell and Developmental Biology, 2018)
There is a growing list of cancer immunotherapeutics approved for use in a population with an increasing number of aged individuals. Cancer immunotherapy (CIT) mediates tumor destruction by activating anti-tumor immune responses that have been silenced through the oncogenic process. However, in an aging individual, immune deregulation is positively correlated with age. In this context, it is vital to examine the age-related changes in the tumor microenvironment (TME) and specifically, those directly affecting critical players to ensure CIT efficacy. Effector T cells, regulatory T cells, myeloid-derived suppressor cells, tumor-associated macrophages, and tumor-associated neutrophils play important roles in promoting or inhibiting the inflammatory response, while cancer-associated fibroblasts are key mediators of the extracellular matrix (ECM). Immune checkpoint inhibitors function optimally in inflamed tumors heavily invaded by CD4 and CD8 T cells. However, immunosenescence curtails the effector T cell response within the TME and causes ECM deregulation, creating a biophysical barrier impeding both effective drug delivery and pro-inflammatory responses. The ability of the chimeric-antigen receptor T (CAR-T) cell to artificially induce an adaptive immune response can be modified to degrade essential components of the ECM and alleviate the age-related changes to the TME. This review will focus on the age-related alterations in ECM and immune-stroma interactions within the TME. We will discuss strategies to overcome the barriers of immunosenescence and matrix deregulation to ameliorate the efficacy of CIT in aged subjects.